Sleep habits, quality and chronotype of Paralympic athletes - Dekkel Bachar; Davidah Koseff; Osnat Fliess Douer (European Federation of Adapted Physical Activity, 2022)
This study aimed to understand the sleeping habits of Israeli Paralympic Athletes as a pre-intervention stage to implement sleep hygiene programs. The Pittsburgh Sleep Quality Index questionnaire was used to assess sleep quality. The Epworth Sleepiness Scale was used to determine sleepiness throughout the day. Chronotype was detected using the Horne and Östberg Questionnaire. Para-athletes who were expected to represent Israel at the Tokyo 2020 games were approached via email. The surveys were collected online between April and August, 2018. Para-athletes (n = 52, male = 32, female = 20, mean age = 31.2y, SD = 11.9, from 13 different sport disciplines) completed the online surveys. One-way ANOVA test was used to compare sleep efﬁciency between the sleepy and non-sleepy groups. MANOVA test was performed to evaluate differences between sleep efficiency, daytime dysfunction and latency between the good and poor sleep quality groups. Non-parametric tests were conducted to analyze the association between the results of the three questionnaires and each sample characteristics. Under a third (31%, n=16) of the athletes slept between 6.5 to 7 hours per night, and a further 29% (n=15) slept less than 6 hours. From the MANOVA analysis, athletes with poor sleep quality had statistically signiﬁcantly lower sleep efﬁciency (p = .028, F(1,50) = 5.11, medium effect size:  = .093), greater daytime dysfunction (p < .001, F(1,50) = 14.19, large effect size:  = .221), and greater sleep latency (p < .001, F(1,50) = 15.08, large effect size:  = .232), than athletes with good sleep quality. Of the athletes, 33% reported having 'moderate to excessive daytime sleepiness', 46% did not train at times that match their chronotype. The results of this study may aid in planning effective intervention methods to improve athletes' sleep quality.